DESAIN MEBEL SARANA KERJA DAN SIMPAN STUDI KASUS: JANJI JIWA - Hafson, Haikal; Hariandini, Tesa beta (Department of Interior Design, Faculty of Engineering, Lancang Kuning University, Indonesia, 2024)
The design of work and storage furniture is an important element in creating a pleasant shopping experience in a mall environment, especially for booths that provide coffee and bread menus such as Janji Jiwa. This research explores furniture design for the Janji Jiwa booth, with a focus on space efficiency, ergonomics and aesthetics that are in harmony with the characteristics of the mall. This design aims to maximize the function of the booth in a limited space while maintaining comfort and ease of access for staff and customers. Key aspects of the design include the selection of durable and easy-to-maintain materials, a layout that supports efficient workflow, and visual elements that reflect the Janji Jiwa brand identity. This design approach also pays attention to integration with mall elements, such as lighting and visitor circulation, to create a consistent and engaging experience. The results of this design are expected to improve booth operations and provide a satisfying and interesting experience for mall visitors, supporting business success and building customer loyalty.